Cytomegalovirus-associated panenteritis in an immunocompetent 60-year-old woman treated with oral valganciclovir: a case report - Kye Whon Kim; Min Cheol Kim (Journal of International Medical Research)
Cytomegalovirus (CMV) infection typically affects immunocompromised individuals. However, CMV-associated enteritis involving the entire small intestine is rare in immunocompetent patients. We report a case of a 60-year-old immunocompetent woman with a history of diabetes mellitus who presented with diarrhea for 3 weeks. Abdominal computed tomography and stool tests revealed panenteritis accompanied by protein-losing enteropathy. Enteroscopy revealed ulcerative mucosa throughout the small intestine, and subsequent biopsies confirmed CMV-associated enteritis. Initial treatment with intravenous ganciclovir was complicated by pancytopenia, leading to its discontinuation and a switch to oral valganciclovir. This adjustment led to significant clinical improvement and symptom resolution. This case highlights the importance of considering CMV-associated enteritis in immunocompetent patients presenting with unexplained gastrointestinal symptoms and demonstrates the effectiveness of oral valganciclovir following ganciclovir-induced pancytopenia.